DAMPAK INFLASI PADA PINJAMAN (QARD) DALAM HUKUM PERNIAGAAN ISLAMI - Desy Wahyuni (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2019)
The occurrence of inflation in the modern era is used by creditors to request additional loans given to debtors. In Islamic economics, loans must be repaid without the determination of the index of commodities, currencies, or any group of currencies. However, someone can lend in the form of gold or other currencies which according to the perception of people are not vulnerable to inflation. Inflation control in Islamic commercial law must be in accordance with mu'amalah validity by using instruments that avoid gharar, usury, qimar and maisir (game of opportunity), and two contracts (contracts) that are interdependent and free mutual agreement, contractual compliance ( contract) with maqasid syariah, profits with obligations, are permitted as general rules.